2021
DOI: 10.1101/2021.01.27.428434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astrocytic VMAT2 in the developing prefrontal cortex is required for normal grooming behavior in mice

Abstract: Astrocytes control synaptic activity by modulating peri-synaptic concentrations of ion and neurotransmitters including dopamine and, as such, can be critically involved in the modulation of some aspect of mammalian behavior. Here we report that genetic mouse model with a reduced medial prefrontal cortex (mPFC) dopamine levels, arising from astrocyte-specific conditional deletion of vesicular monoamine transporter 2 (VMAT2; aVMTA2cKO mice) shows excessive grooming and anxiety-like behaviour. The VMAT2cKO mice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…A novel mRNA splice variant of Drosophila VMAT (DVMAT‐B) has been found in a small subset of glia in the lamina of the fly's optic lobe (Romero‐Calderón et al, 2008), but it is only very recently that an immunohistochemistry survey of various brain areas has revealed that VMAT2 immunolabeling is particularly enriched in the astrocytes of the frontal cortex (including the PFC) in rodents and humans (Petrelli et al, 2020, 2021). The rodent immunosignal is visible in astrocytes from the second postnatal week, but almost absent in other DAergic areas such as the striatum and ventral tegmental area, which suggests that astrocytic VMAT2 plays a specific functional role in frontal cortical regions.…”
Section: Functional Role Of Astrocytes In the Regulation Of Glutamate...mentioning
confidence: 99%
“…A novel mRNA splice variant of Drosophila VMAT (DVMAT‐B) has been found in a small subset of glia in the lamina of the fly's optic lobe (Romero‐Calderón et al, 2008), but it is only very recently that an immunohistochemistry survey of various brain areas has revealed that VMAT2 immunolabeling is particularly enriched in the astrocytes of the frontal cortex (including the PFC) in rodents and humans (Petrelli et al, 2020, 2021). The rodent immunosignal is visible in astrocytes from the second postnatal week, but almost absent in other DAergic areas such as the striatum and ventral tegmental area, which suggests that astrocytic VMAT2 plays a specific functional role in frontal cortical regions.…”
Section: Functional Role Of Astrocytes In the Regulation Of Glutamate...mentioning
confidence: 99%
“…Interestingly, the astrocytes in this model expressed high levels of VMAT2, which do not seem to be present in astrocytes in the SNpc [ 41 ], but only in the prefrontal cortex of mice and potentially humans [ 42 , 43 ]. This suggests that the culture might contain a population of astrocytes resembling the population the dopaminergic neurons project to, rather than the astrocytes in the SNpc.…”
Section: Discussionmentioning
confidence: 99%
“…While a large body of work has identified perturbations in neuronal genes and proteins that affect synaptic connectivity (Figures 2A,B; Gauthier et al, 2010;Marín, 2012;Nieto et al, 2013;Volk and Lewis, 2013;El-Ansary and Al-Ayadhi, 2014;McAllister, 2014;English et al, 2015;Estes and McAllister, 2015;Sinclair et al, 2016;Ishizuka et al, 2017;Gao et al, 2018;Jiang et al, 2018;Huang et al, 2019;Trossbach et al, 2019;Wiebe et al, 2019;Barbosa et al, 2020;Chen et al, 2020;Boukouaci et al, 2021), accumulating evidence indicates that microglia are also key loci of dysfunction in neurodevelopmental disorders (Koyama and Ikegaya, 2015;Jin et al, 2017;Comer et al, 2020;Petrelli et al, 2020;Xu et al, 2020). In ASD and SZ, mPFC microglia have amoeboid morphology and increased cytokine production that is characteristic of an activated state (Fillman et al, 2013;Momtazmanesh et al, 2019).…”
Section: Roles Of Microglia In Disease Onset and Progressionmentioning
confidence: 99%
“…Indeed, microglial depletion and repopulation can alter astrocyte gene expression (Coleman et al, 2020). Perturbation of astrocyte function has been implicated in ASD and SZ (Trépanier et al, 2016;Tarasov et al, 2020;Zhang et al, 2020;Notter, 2021;Wang et al, 2021;Allen et al, 2022) and astrocyte dysfunction in PFC has been implicated in inducing anxiety-like behaviors (Li et al, 2021) and cognitive impairment (Brockett et al, 2018;Petrelli et al, 2020), making the PFC of particular interest for studying astrocyte-microglial interactions.…”
Section: Looking Ahead: Future Research and Unanswered Questionsmentioning
confidence: 99%